Early Invasive Strategy and In‐Hospital Survival Among Diabetics With Non‐ST‐Elevation Acute Coronary Syndromes: A Contemporary National Insight. Issue 3 (18th March 2017) - Mahmoud, Ahmed N.; Elgendy, Islam Y.; Mansoor, Hend; Wen, Xuerong; Mojadidi, Mohammad K.; Bavry, Anthony A.; Anderson, R. David
Abstract : Background: There are limited data on the merits of an early invasive strategy in diabetics with non‐ST‐elevation acute coronary syndrome, with unclear influence of this strategy on survival. The aim of this study was to evaluate the in‐hospital survival of diabetics with non‐ST‐elevation acute coronary syndrome treated with an early invasive strategy compared with an initial conservative strategy. Methods and Results: The National Inpatient Sample database, years 2012–2013, was queried for diabetics with a primary diagnosis of non‐ST‐elevation acute coronary syndrome defined as either non‐ST‐elevation myocardial infarction or unstable angina (unstable angina). An early invasive strategy was defined as coronary angiography±revascularization within 48 hours of admission. Propensity scores were used to assemble a cohort managed with either an early invasive or initial conservative strategy balanced on >50 baseline characteristics and hospital presentations. Incidence of in‐hospital mortality was compared in both groups. In a cohort of 363 500 diabetics with non‐ST‐elevation acute coronary syndrome, 164 740 (45.3%) were treated with an early invasive strategy. Propensity scoring matched 21 681 diabetics in both arms. Incidence of in‐hospital mortality was lower with an early invasive strategy in both the unadjusted (2.0% vs 4.8%; odds ratio [OR], 0.41; 95% CI, 0.39–0.42; P <0.0001) and propensity‐matched models (2.2% vs 3.8%; OR, 0.57; 95% CI, 0.50–0.63; P <0.0001). The benefit was observed across various subgroups, except for patients with unstable angina ( P interaction =0.02). Conclusions: An early invasive strategy may be associated with a lower incidence of in‐hospital mortality in patients with diabetes. The benefit of this strategy appears to be superior in patients presenting with non‐ST‐elevation myocardial infarction compared with unstable angina.